Huhh1 Rockglacier Evolution Experiment 1 * A and 0*Acc - Müller, Johann; Gaertner-Roer, Isabelle; Vieli, Andreas (Copernicus Publications, 2016)
Perturbation Experiment. Stept after Rockglacier Built-Up (1000yrs). Flow Rate Factor change 1.7A and No Accumulation 0*Acc